How Governance Can Contribute to Amazon Biome Conservation? - Fernandes, Carolina Cristina; Marcovitch, Jacques; Pinto, Karen Esteves Fernandes (Environmental Management and Sustainable Development, 2024)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Forest conservation has transcended environmental concerns and become a determining factor in global social and economic issues. Therefore, setting forest conservation goals, including recovery and/or reforestation, is critical to help mitigate global warming and climate change. Although Amazonian countries have forestry policies for forest conservation, the forest continues to be degraded. The aim of this article is to suggest a regional governance model for the nine countries that share the Amazon rainforest. The thesis of the paper is that the definition of a common legal basis for the nine countries can contribute to forest conservation. Through qualitative analysis of exploratory and descriptive variables, the main topics related to the proposal of a governance model were identified. Multi-level governance contributes to the environmental conservation process by creating an environment to engage local, national, and international stakeholders from diverse groups. As a result of this paper, we suggest the creation of a supranational governance, composed and regulated by each of the nine countries of the Amazon biome and having as reference the AFR100 initiative. The proposition and creation of governance among Amazonian countries are fundamental for achieving the objectives for the conservation of the biome; such governance must take into account existing public policies, institutional mechanisms, and financial commitments. Although the Amazon countries present a framework of policies and commitments that seek to preserve the biome, the reality is that forest degradation through deforestation with negative effects on the climate and on the communities that depend on the standing forest still exists.